2007
DOI: 10.1111/j.1365-2559.2007.02785.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiogenesis in myocardial remodelling after infarction

Abstract: Aims:The lymphatic system is involved in fluid homeostasis of the cardiac interstitium, but lymphangiogenesis in myocardial remodelling has not previously been examined histopathologically. The aim was to investigate by D2-40 immunohistochemistry the sequential changes in lymphatic distribution in the process of myocardial remodelling after myocardial infarction (MI). Methods and results: Myocardial tissues in various phases of healing after MI were obtained from 40 autopsied hearts. D2-40+ lymphatic vessel de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 28 publications
5
81
0
3
Order By: Relevance
“…After MI, the number and diameter of cardiac lymphatic vessels increase. Lymphangiogenesis occurs after MI 35. Enhancement of lymphangiogenesis may reduce myocardial oedema and cardiac fibrosis, promoting improvement in cardiac function 36, 37.…”
Section: Discussionmentioning
confidence: 99%
“…After MI, the number and diameter of cardiac lymphatic vessels increase. Lymphangiogenesis occurs after MI 35. Enhancement of lymphangiogenesis may reduce myocardial oedema and cardiac fibrosis, promoting improvement in cardiac function 36, 37.…”
Section: Discussionmentioning
confidence: 99%
“…after AMI (Ishikawa et al, 2007). They found that newly formed lymphatic vessels first appeared in the early stages of granulation, subsequently increased in the late stages, and remained up to the scar phase.…”
Section: Figurementioning
confidence: 99%
“…Because our enrichment method enabled the efficient detection of low abundant glycoproteins in plasma, it may be possible to use this technique to identify N-glycosylated biomarkers and potential therapeutic targets in human patient samples. Indeed, our analyses of human plasma from heart disease patients revealed the presence of lymphatic vessel endothelial hyaluronic acid receptor 1 (LYVE1), a lymphangiogenic glycoprotein which is reportedly involved in myocardial remodeling after infarction (68,69). Our novel PUC-ERLIC approach may therefore enable the detection of cardiac glycoproteins involved in myocardial healing, and could potentially be used to identify biomarkers of distinct clinical outcomes in patients undergoing heart surgery.…”
Section: Enrichment Of Plasma Soluble and Vesicular Glycoproteinsmentioning
confidence: 99%